ANALISIS PERMINTAAN SEPEDA MOTOR DI KOTA JAMBI - M Zahari MS (Universitas Batanghari Jambi, 2011)
This research aim to to know how influence of earnings of perkapita society to motorbike request in town Jambi, To know how influence sum up the resident to motorbike request in town Jambi, To know how price influence to motorbike request in town JambiData used is data sekunder with the type of data of time series 10 year from year 2000-2009. Data steming from BPS ( Statistical Center Body), library, and other source like journal and previous research pickings with the Earnings of perkapita society, growth of resident and price as variable independent influencing request to motorbike as variable dependent.Result of this examination prove that Earnings of perkapita society have an effect on positive but not signifikan to level of amount of request of motorbike of brand, Resident Growth have an effect on positive and signifikan to level of amount of request of motorbike in Town Jambi, Price have an effect on the negativity and signifikan to level of amount of request of motorbike in Town Jambi